2007
DOI: 10.1182/blood-2007-01-071340
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils contribute to innate antiviral immunity and promote clearance of respiratory syncytial virus

Abstract: Eosinophils are recruited to the lungs in response to respiratory syncytial virus (RSV) infection; however, their role in promoting antiviral host defense remains unclear. Here, we demonstrate that eosinophils express TLRs that recognize viral nucleic acids, are activated and degranulate after singlestranded RNA (ssRNA) stimulation of the TLR-7-MyD88 pathway, and provide host defense against RSV that is MyD88 dependent. In contrast to wild-type mice, virus clearance from lung tissue was more rapid in hypereosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
257
4
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(279 citation statements)
references
References 56 publications
3
257
4
8
Order By: Relevance
“…Taken together, these results suggest that TLR4 actually does not have a crucial, indispensable function in promoting host defense against a natural respiratory virus infection. However, other pattern recognition receptors (e.g., TLR3 [36], TLR7 [37]) have been explored vis à vis their role in promoting host defense against respiratory syncytial virus challenge, and might be intriguing subjects for future study with the natural PVM pathogen model.…”
Section: Role Of Tlr4mentioning
confidence: 99%
“…Taken together, these results suggest that TLR4 actually does not have a crucial, indispensable function in promoting host defense against a natural respiratory virus infection. However, other pattern recognition receptors (e.g., TLR3 [36], TLR7 [37]) have been explored vis à vis their role in promoting host defense against respiratory syncytial virus challenge, and might be intriguing subjects for future study with the natural PVM pathogen model.…”
Section: Role Of Tlr4mentioning
confidence: 99%
“…In mice undergoing a primary RSV infection, it has been found that eosinophils contribute to viral clearance [61]. This has not been directly tested in mice undergoing a memory response to RSV, however, work from vacvF-immunized mice and IL-13-deficient vacvG-immunized mice, neither of which develop pulmonary eosinophilia, demonstrate that viral clearance is not significantly altered in the absence of eosinophils [44,52].…”
Section: The Relationship Between Pulmonary Eosinophilia and Systemicmentioning
confidence: 99%
“…[19,20]. Chez la souris, il n'existe qu'une seule étude publiée sur l'expression des TLR sur les éosinophiles murins ; elle a mis en évidence la présence des TLR 3, 4, 5 et 7 [21]. L'expression par les éosinophiles de ces différents récepteurs de l'immunité innée, et la reconnaissance de l'appartenance de …”
Section: Reconnaissance Directe Des Pathogènes Par Les éOsinophilesunclassified
“…In vitro, le même phénomène est observé après infection par le RSV (respiratory syncytial virus). Phipps et ses collaborateurs ont montré de manière indirecte que les éosinophiles améliorent l'élimination du virus via un processus dépendant de TLR7 et MyD88 [21]. Lors d'une infection par le virus de l'immunodéficience humaine (VIH), l'éosinophile peut constituer à la fois un réservoir de virus, puisque cette cellule est infectable via l'antigène CD4 qu'elle exprime, mais elle peut aussi participer à l'activité antivirale via la libération d'EPO et d'H2O2, ce qui illustre parfaitement le concept de dualité fonctionnelle de l'éo-sinophile [25].…”
Section: éOsinophiles Et Infectionsunclassified